A preliminary stylometric analysis of the Four Gospels in order to prove literary independence instead of the Synoptic Problem - Christianto, Victor (Sekolah Tinggi Teologi Satyabhakti, East Java, 2024)
As we discussed in a forthcoming article, there is an alternative hypothesisthat can be considered in lieu of the so-called Baur’s Tuebingen school, thatis the formative years of Earliest Christianity led to such notion of synthesisbetween Petrine Christianity and Pauline Christianity. Instead, we consider a branching process, which can be considered alternatively as spreadingnetwork even to Asia and Europe at the time. Corresponding to the hypothesis is that the four witnesses who worked on at the period to write down the four Gospels were more likely to write independently. In the meantime, this hypothesis does not exclude possibility that they ever met in person, at the First Council in Jerusalem as depicted in the book of Acts chapter 15, or before, or after that event.